The structure and evolution of the African air transport network - Snaddon, David (Department of Statistical Sciences, 2026)
This dissertation studies the structure and evolution of the African Air Transport Network (AATN) from 2015 to 2023. With respect to the network's structure, a power-law distribution appropriately characterises the networks degree distribution. The ‘golden tri-angle' between Johannesburg O.R. Tambo, Cape Town, and Durban King Shaka plays a dominant role in the network's structure when considering airline seat capacity. Addis Ababa shows strong growth in node centrality, ending the period with the highest centrality across all observed centrality measures. Community detection reveals airport clusters that align with geographic regions, including African subregions and countries. k-coredecomposition reveals a growing core of the network spread across the continent with a higher concentration in West Africa. Longitudinal trends of network-wide indicators de-tail the network's evolution. A gradual decrease in the average clustering coefficient and degree assortativity coefficient but an increase in the Gini coefficient and largest degree suggest that the network aligns to a growing airline hub-and-spoke structure. During this period, the COVID-19 pandemic occurs and significantly affects the network's evolution, particularly in measures related to the sizing of the network, calling for an investigation into the changes from pre-pandemic to the end of recovery phase. When the network recovers, it does not revert back to its pre-pandemic structure completely, adding new routes and not reintroducing some old ones. Moreover, a similar magnitude of variability during the period is found in the global air transport network.